Hav, hage, teater og temperatur i Cora Sandels Alberte-bøker - Bartnæs, Morten (Nordlit, 2010)
Current readings of Cora Sandel’s Alberta-trilogy (1926-1939) frequently tend to reuse the novels’ imagery in their own descriptive and interpretive statements – instead of treating this characteristic of the novels with the same degree of attention as, e.g., the trilogy’s psychological and political aspects, or its narrative technique. The present article attempts to draw attention to the trilogy’s imagery as a both autonomous and integral element in Cora Sandel’s novelistic art. Three metaphorical ways of thought which show their presence throughout the trilogy, are singled out: In the novels, the persons (and thus, implicitly or explicitly, the human condition) are frequently pictured as being situated on the high sea, in a garden or in a theatre. In the Alberta-trilogy, these time-honoured metaphors are the object of a refined practice of re-contextualization. In my attempt to trace this process, I draw special attention to the relationship between these metaphorical fields and the trilogy’s pervasive use of thermal imagery. In each case, I attempt to show that the thermal descriptions that are associated with the metaphorical views of human existence as a boat trip, a garden sojourn or a theatre performance have a central function in Cora Sandel’s use of these images.
Keywords: Cora Sandel; Alberta; Alberte; termisk; bilde; kulde; metafor; metaforikk